PLEASE HELP ASAP!!! CORRECT ANSWERS ONLY PLEASE!!
Subract and simplify.
![PLEASE HELP ASAP CORRECT ANSWERS ONLY PLEASE Subract and simplify class=](https://us-static.z-dn.net/files/d78/67d7cd0252e5d8d84dd9b1f4b35185e3.png)
Answer: C
Step-by-step explanation:
[tex]\dfrac{x+1}{x-5} - \dfrac{x-2}{x+3}[/tex]
= [tex]\dfrac{x+1}{x-5}(\dfrac{x+3}{x+3}) - \dfrac{x-2}{x+3}(\dfrac{x-5}{x-5})[/tex]
= [tex]\dfrac{x^{2}+4x+3}{(x-5)(x+3)} - \dfrac{x^{2}-7x+10}{(x-5)(x+3)}[/tex]
= [tex]\dfrac{x^{2}+4x+3-(x^{2}-7x+10)}{(x-5)(x+3)}[/tex]
= [tex]\dfrac{11x-7}{(x-5)(x+3)}[/tex]